The Impact of Physical Store Strategy Changes on Sales Performance and Customer Loyalty: Evidence from Retail Store X - Amelia Tryastuti; Mochamad Solichin (Jurnal Maksipreneur, 2026)
This study examines the impact of changes in physical store strategy on sales performance and customer loyalty at Retail Store X amid increasing competition and shifting consumer expectations in the retail industry. As offline stores evolve beyond transactional spaces, strategic adjustments are required to enhance customer experience and sustain competitiveness. This research employs a quantitative approach, collecting data through structured questionnaires distributed to customers of Retail Store X. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software to evaluate the relationships among changes in physical store strategy, sales performance, and customer loyalty. The results indicate that changes in physical store strategy have a positive and significant effect on customer loyalty, whereas sales performance has a stronger influence on sustaining long-term customer loyalty. These findings suggest that customer loyalty is formed through a continuous process that integrates positive in-store experiences with consistent sales outcomes. The study provides practical implications for retail managers to balance experiential strategies and performance-oriented initiatives in offline retail settings, while also contributing to the literature on retail management and customer behavior.